Short term impact of smoke-free legislation in England: retrospective analysis of hospital admissions for myocardial infarction. (8th June 2010) - Sims, Michelle; Maxwell, Roy; Bauld, Linda; Gilmore, Anna
Abstract : Objective To measure the short term impact on hospital admissions for myocardial infarction of the introduction of smoke-free legislation in England on 1 July 2007. Design An interrupted time series design with routinely collected hospital episode statistics data. Analysis of admissions from July 2002 to September 2008 (providing five years' data from before the legislation and 15 months' data from after) using segmented Poisson regression. Setting England. Population All patients aged 18 or older living in England with an emergency admission coded with a primary diagnosis of myocardial infarction. Main outcome measures Weekly number of completed hospital admissions. Results After adjustment for secular and seasonal trends and variation in population size, there was a small but significant reduction in the number of emergency admissions for myocardial infarction after the implementation of smoke-free legislation (−2.4%, 95% confidence interval −4.06% to −0.66%, P=0.007). This equates to 1200 fewer emergency admissions for myocardial infarction (1600 including readmissions) in the first year after legislation. The reduction in admissions was significant in men (3.1%, P=0.001) and women (3.8%, P=0.007) aged 60 and over, and men (3.5%, P<0.01) but not women (2.5% P=0.38) aged under 60. Conclusion This study adds to a growing body of evidence that smoke-free legislation leads to reductions in myocardial infarctions. It builds on previous work by showing that such declines are observed even when underlying reductions in admissions and potential confounders are controlled for. The considerably smaller decline in admissions observed in England compared with many other jurisdictions probably reflects aspects of the study design and the relatively low levels of exposure to secondhand smoke in England before the legislation.